'Exploring the "Construction" strand in the Irish Primary School Visual Arts Curriculum through the Forest School approach'. Issue 3 (3rd July 2018) - Murphy, Marie Claire
ABSTRACT: Forest School is a concept, or intervention to traditional educational settings, backed up by research and built upon long-standing theories that children engage with nature naturally and that learning becomes more relevant to the student when they can relate it to real life scenarios. This research documents the implementation of the Irish Primary School Visual Arts Curriculum through Forest School, specifically, the 'Construction' Strand. The research was a qualitative inquiry that was supported by an action research methodology. It was conducted over six weekly sessions. Key findings show the development of a sense of responsibility, resilience, independence, happiness in a sense of achievement and an awakened awareness of the child's own surroundings. The findings advocate the benefits of implementing this approach to enhance the Primary School Visual Arts Curriculum, as well as promoting happiness and contentment in the remainder of the day at school in other curricular subjects. .